Case Report: Infantile hypercalcemia type 1 due to CYP24A1 pathogenic variants—three adult patients with nephrolithiasis and nephrocalcinosis successfully treated with fluconazole - Nikolina Vucenovic Basic; Bodo Beck; Annemarie Balasko; Ivana Vukovic Brinar; Margareta Fistrek Prlic (Frontiers in Medicine, 2026)
Infantile hypercalcemia type 1 (HCINF1) is a rare genetic disorder caused by pathogenic variants in the CYP24A1 gene, which encodes the vitamin D–catabolic enzyme 24-hydroxylase responsible for inactivating 1,25-dihydroxyvitamin D₃. The clinical presentation ranges from severe forms diagnosed in infancy—characterized by hypercalcemia, dehydration, and vomiting—to milder forms that are often identified in adulthood during evaluation for recurrent nephrolithiasis. We present two adult female patients with late-onset HCINF1, both initially referred to a nephrologist for nephrolithiasis and nephrocalcinosis, and one male patient with an infantile presentation who began fluconazole therapy in adulthood. This case series highlights rare late-onset manifestations of HCINF1 associated with recurrent nephrolithiasis, secondary distal renal tubular acidosis (dRTA), and variable degrees of renal function impairment. It emphasizes the importance of considering genetic testing in adults with unexplained hypercalcemia and nephrolithiasis and supports the therapeutic role of fluconazole in selected cases.